Endotoxin removal therapy with Polymyxin B immobilized fiber column as a COVID-19-bedside strategy protocol for endotoxic shock - De Rosa, Silvia; Zanella, Monica; Samoni, Sara; Ronco, Claudio (Frontiers in Nephrology, 2022)
Endotoxin-induced sepsis is a leading cause of ICU mortality. From 1994 to the present, PMX-HP has been available as an adjuvant therapy for endotoxin removal and immunomodulation. The efficacy and usefulness of this therapy have been demonstrated for more than a quarter of a century and are partially supported by clinical studies. However, it appears that selected subgroups of patients with endotoxic shock and with appropriate timing could benefit. Endotoxemia may be involved in the pathophysiology of COVID-19, based on enterocyte dysfunction and malabsorptive syndrome. Due to the characteristics of the microbiota, Gram-negative bacteria or their fragments (i.e., endotoxin) may translocate into the systemic circulation leading to inflammatory activation, immune dysfunction, and sepsis. In addition, patients with severe forms of COVID-19 are at risk of superimposed infections. Endotoxemia can arise due to the translocation of Gram-negative bacteria or their fragments from the gut barrier. According to the most updated evidence available from large randomized trials, septic shock patients with MODS > 9 and EA levels ranging from 0.6 to 0.9 are those who may benefit the most from PMX‐HP treatment in terms of improvement of survival. As shown in a previous publication, we believe that similarly to the source control, microbiological cultures, and antibiotics administration, EA evaluation at regular intervals, and the targeted use of PMX‐HP could be lifesaving and adequate within the golden hour for the diagnosis and treatment of endotoxic shock. In our center, we applied a diagnostic-clinical flowchart also for endotoxic shock related to COVID-19.